The Determination of Acoustical Absorbing Materials in The â€œAl-Marwahâ€ Room of â€œAl-Akbarâ€ Mosque in Surabaya using Objective Parameters Approximation - A. Asmoro, Wiratno (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
The room that used to hold the speech activity needs a good acoustical quality. To determine the acoustical quality of a room the experimental research was conducted to find the relationship between the determination of acoustical absorbing materials and speech intelligibility in the â€œAl-Marwahâ€ room of â€œAl-Akbar mosque in Surabaya. Through the monaural acoustical measurements, the objective acoustical parameters in the â€œAl-Marwahâ€ room can be found from impulse responses. Then we can use it to determine the acoustical absorbing materials in the room. Considering the acoustical parameters of RT, EDT, D50, C50, and %Alcons at several positions, we can find the relationships between those parameters. The result, then, could be used to properly judge the acoustical absorbing materials which should be applied in the room. For the acoustical treatments on the ceiling of 376 m2 and the pillars of 373 m2 in the â€œAl-Marwahâ€ room of the â€œAl-Akbarâ€ mosque, the average values of RT and EDT un mid-band frequencies were found 5.52 sec and 7.88 sec respectively; whereas the values of D50, C50 and %Alcons were found in the range of 3.25 ï¾ 10.5%, -15 ï¾ -9,4 dB and 15 ï¾ 21% respectively. Those condition produce speech intelligibility on Poor to Sufficient category.